2021
DOI: 10.22159/ijpps.2021v13i7.41204
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Floating Microspheres of Ciprofloxacin by Solvent Evaporation Method Using Different Polymers

Abstract: Objective: The main intention of this research was to formulate and evaluate floating microspheres of ciprofloxacin using different polymers to prolong gastric residence time. Methods: The microspheres were formulated by the solvent evaporation method using different ratios of polymers like carbopol 940, ethylcellulose, and Hydroxy Propyl Methyl Cellulose K4M. Further, the floating microspheres were evaluated for micromeritic properties like bulk density, tapped density, angle of repose, etc., percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Improved release of ciprofloxacin hydrochloride in acidic pH has been reported and hence a formulation of ciprofloxacin that could swell so that is retained in a fed stomach was designed [17]. Also, it was reported that ciprofloxacin showed reduced bioavailability from the colon (pH 7.4) in an in vitro study of slow-release release ciprofloxacin in intestinal model [18].…”
Section: Formulationsmentioning
confidence: 99%
“…Improved release of ciprofloxacin hydrochloride in acidic pH has been reported and hence a formulation of ciprofloxacin that could swell so that is retained in a fed stomach was designed [17]. Also, it was reported that ciprofloxacin showed reduced bioavailability from the colon (pH 7.4) in an in vitro study of slow-release release ciprofloxacin in intestinal model [18].…”
Section: Formulationsmentioning
confidence: 99%
“…Perolehan kembali diperoleh dari rasio antara bobot mikrosfer yang dihasilkan dengan bobot total bahan yang digunakan dan dihitung dalam persen [11]. Pengujian ini dilakukan untuk menganalisis perbedaan laju alir pada proses spray drying terhadap perolehan hasil mikrosfer.…”
Section: Perolehan Kembaliunclassified
“…La harina de pulpa de coco es aquella hecha del subproducto de la obtención de leche de coco, esta harina no posee gluten, pero si alto contenido de fibra que puede considerarse potencialmente como alimento funcional Erminawati et al (2017). Esta fibra se relaciona con varios efectos fisiológicos y metabólicos; por ejemplo, en el tracto digestivo la fibra dietética ejerce un efecto amortiguador que vincula el exceso de ácido en el estómago aumentando el volumen fecal y estimulando la evacuación intestinal, además, proporciona un ambiente favorable para el crecimiento de la flora intestinal beneficiosa (Arumugam et al, 2015); por lo indicado actualmente las personas son más conscientes del consumo de alimentos saludables. La harina de coco puede ser utilizada como material para sustituir la harina de trigo en la elaboración de pan, fideos y galletas Dat y Phuong (2017).…”
unclassified